Intergenerational risk sharing in the spirit of Arrow, Debreu, and Rawls, with applications to social security design - Laurence Ball; N. Gregory Mankiw (The Johns Hopkins University, Department of Economics, 2002)
This paper examines the optimal allocation of risk in an overlapping-generations economy It compares the allocation of risk the economy reaches naturally to the allocation that would be reached if generations behind a Rawlsian 'veil of ignorance' could share risk with one another through complete Arrow-Debreu contingent-claims markets The paper then examines how the government might implement optimal intergenerational risk sharing with a social security system One conclusion is that the system must either hold equity claims to capital or negatively index benefits to equity returns
Keywords: 330; Risiko; Allokation; Overlapping Generations; Allgemeines Gleichgewicht; Gesetzliche Rentenversicherung; Theorie